Upaya Guru Tahfidz Dalam Meningkatkan Hafalan Al-Qur’an Peserta Didik Di SMP IT MTA Karanganyar - Hartati, Widiya; Salim, Hakimuddin (Kamaya: Jurnal Ilmu Agama, 2025)
Al-Qur'an was revealed as a guide for all humans throughout time until the end of time. Therefore, the Koran must be maintained and guarded so that Muslims will not lose its guidance, namely by grounding it. Grounding Al-Qur'an means making efforts to be planned and systematic. Allah SWT asks mankind to preserve the Koran by memorizing it. This is a challenge that must be carried out by tahfidz teachers. The aim of this research is to find out what efforts should be made to improve students' memorization at SMP IT MTA Karanganyar. The approach used is qualitative which includes direct interaction with participants through the case study method. Data was collected through interviews, observation and document analysis. Data comes from tahfidz teachers while secondary data sources come from theses, journals and other supporting documents. Source triangulation is a method for verifying the validity of data by examining data obtained through triangulation of techniques and sources. The stages carried out are the process of data reduction, data presentation and drawing conclusions. The results obtained at SMP IT MTA Karanganyar were that teachers gave students freedom to memorize the Al-Qur'an, students were given freedom to choose the appropriate memorization method without ignoring the main goal of memorization. Apart from improving students' memorization of the AL-Qur'an, this learning activity can also be a spiritual process that requires dedication, consistency and sincerity of intention. The freedom in choosing the memorization method given by the tahfidz teacher to students does not rule out the possibility that the tahfidz teacher must also actively guide and monitor the development of students' memorization.